Evaluation of the Quality of Clinical Education Based on the Perspective of Medical Students of Shahroud University of Medical Sciences - Akbari Farmad 1, Somayeh; Davardoost 2*, Nahid; Sadeghian 3, Faride; Khodaei 4, Fatemeh (Shahroud Journal of Medical Sciences, 2020)
Background: Improving the quality of clinical education requires a continuous review of the existing situation to identify strengths and weaknesses. The aim of the study was to evaluate the quality of clinical education based on the perspective of medical students of Shahroud university of medical sciences.Methods: This descriptive-analytical study was conducted at1397-98. Participants were 230 medical students and interns in Shahroud university of medical sciences who were enrolled in the study. The data were collected using the clinical education quality assessment questionnaire, with a range of 0-66 points and divided into three levels: weak, moderate and desirable. T-test was used for data analysis. The Significanl level was set at 0.05.Results: The results showed that the mean of the standard deviation of clinical education quality in terms of goals and curriculum (12.95), teacher performance (10.23), and student treatment (4.09) was desirable from medical students' point of view. (Given that the significance level is less than 0.05, these averages are desirable) while in terms of educational environment (4.60) and supervision and evaluation (4.01), it is not desirable.Conclusions: According to the findings, clinical quality status is desirable in most aspects, but it is necessary to eliminate the weaknesses to improve the quality of clinical education in this university in terms of the educational environment, monitoring and evaluation according to the students' viewpoints.Keywords: Quality, Clinical education, Medical students.